Focal adhesion kinase activation limits efficacy of Dasatinib in c‐Myc driven hepatocellular carcinoma. (28th October 2018) - Liu, Xianqiong; Song, Xinhua; Zhang, Jie; Xu, Zhong; Che, Li; Qiao, Yu; Ortiz Pedraza, Yunuen; Cigliano, Antonio; Pascale, Rosa M.; Calvisi, Diego F.; Liu, Yanju; Chen, Xin
Abstract: Hepatocellular carcinoma (HCC) is a deadly malignancy with limited treatment options. Recently, it was found that Dasatinib treatment led to synthetic lethality in c‐Myc high‐expressing human cancer cells due to inhibition of p‐Lyn. Overexpression of c‐Myc is frequently seen in human HCC. We investigated the sensitivity to Dasatinib in vitro using HCC cell lines and in vivo using c‐Myc mouse HCC model. We found that HCC cell line responsiveness to Dasatinib varied significantly. However, there was no correlation between c‐Myc expression and IC50 to Dasatinib. In c‐Myc‐induced HCC in mice, tumors continued to grow despite Dasatinib treatment, although the eventual tumor burden was lower in Dasatinib treatment cohort. Molecular analyses revealed that Dasatinib was effective in inhibiting p‐Src, but not p‐Lyn, in HCC. Importantly, we found that in HCC cell lines as well as c‐Myc mouse HCC, Dasatinib treatment induced up regulation of activated/phosphorylated (p)‐focal adhesion kinase(FAK). Concomitant treatment of HCC cell lines with Dasatinib and FAK inhibitor prevented Dasatinib‐induced FAK activation, leading to stronger growth restraint. Altogether, our results suggest that Dasatinib may have limited efficacy as single agent for HCC treatment. Combined treatment with Dasatinib with FAK inhibitor might represent a novel therapeutic approach against HCC. Abstract : Activation of FAK confers resistance to Dasatinib treatment in HCC. Combined treatment with Dasatinib with FAK inhibitor might represent a novel therapeutic approach against HCC.